(untitled) (Eurasian Medical Research Periodical, 2026)
This article is devoted to the identification of morphological changes that occur in the histotopography of the ovaries in girls in the early postpartum period. As a material, the ovaries of girls whose abdomen died of asphyxia and pneumopathy were studied using methods of general histology, histochemistry and morphometry. It was noticed that in the cortical layer of the ovary of newborns, rudimentary eggs are located in a dense state, follicular structures are formed as a result of the proliferation of granulose cells in the areas bordering the stratum corneum, and between them, i.e. in the interstitium, there are pregranular and celemic cells of different densities. It was found that by the age of 3 months in infants, the primary eggs in the ovarian mucosa are thinning, most of them undergo degenerative and destructive changes, bundles of fibrous connective tissue are formed in the intermediate tissue. From the earliest postpartum period, infants experience destruction and atresia of a part of the embryonic eggs that perform a reproductive function in the ovary, granulosis and proliferation of cells of the uterine tissue in the intermediate tissue